2017
DOI: 10.1088/1741-4326/aa68e9
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control design for non-inductively sustained scenarios in NSTX-U using TRANSP

Abstract: This paper examines a method for real-time control of non-inductively sustained scenarios in NSTX-U by using TRANSP, a time-dependent integrated modeling code for prediction and interpretive analysis of tokamak experimental data, as a simulator. The actuators considered for control in this work are the six neutral beam sources and the plasma boundary shape. To understand the response of the plasma current, stored energy, and central safety factor to these actuators and to enable systematic design of control al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Furthermore, much progress has been made on the development of new algorithms for advanced control applications (e.g. [31][32][33][34][35]), including current and rotation profile, snowflake divertor control, and power/particle exhaust handling.…”
Section: Plasma Boundary Shape Control and Realtime Equilibrium Recon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, much progress has been made on the development of new algorithms for advanced control applications (e.g. [31][32][33][34][35]), including current and rotation profile, snowflake divertor control, and power/particle exhaust handling.…”
Section: Plasma Boundary Shape Control and Realtime Equilibrium Recon...mentioning
confidence: 99%
“…maintaining specified gaps between the plasma and PFCs) and for establishing plasma stability and evolution. For example, in [31,35], simulations with the integrated modeling code TRANSP showed that modifying the plasma shaping can be used as a virtual actuator to actively control the current profile in NSTX-U by affecting bootstrap current and beam current drive profiles.…”
Section: Plasma Shape Control System Roles and Requirementsmentioning
confidence: 99%
“…Expert files are external coding that are linked to the main executable and that allow users to manipulate the simulations by including additional features. A direct application of expert files is for simulations dedicated to develop control algorithms and it has been applied on NSTX-U for control of the plasma performance [14,15] and of plasma rotation [16] with Neutral Beam Injection. In this respect expert files can provide valuable inputs for control requirements, diagnostic sensitivity or development of actuator power sharing control algorithms, because they allow the study of the plasma response to external perturbations in the presence of high-fidelity physics models.…”
Section: Calculation Of Ntm Stability In Transp With Simulated Ec Fementioning
confidence: 99%
“…While earlier efforts to implement feedback control in TRANSP relied on injecting custom run-specific FORTRAN code into TRANSP runs [15,26,[34][35][36], the new approach enables any external code to control plasma parameters during a TRANSP run through a socket connection interface. This added flexibility reduces the development time for testing control algorithms and will enable software-in-the-loop testing of plasma control algorithms.…”
Section: Closed Loop Control Simulation Frameworkmentioning
confidence: 99%
“…The beam slowing down time and the energy confinement time (each on the order of 10-100 ms) tend to smooth the effect of the modulations. The beam modulation scheme was simulated in closed loop TRANSP simulations of NSTX-U in [35] where small oscillations in stored energy were observed since the energy confinement time and minimum on/off times were close in that case. However, the controller performance was not significantly impacted by these oscillations.…”
Section: Actuators Measurements and Disturbancesmentioning
confidence: 99%